Ebenacobius Haran, a new southern African genus of flower weevils (Coleoptera: Curculioninae: Derelomini) associated with dicotyledonous plants - Haran, Julien; Benoit, Laure; Procheş, Şerban; Kergoat, Gael J. (European Journal of Taxonomy, 2022)
A new genus of derelomine flower weevil (Curculionidae: Derelomini sensu Franz 2006), Ebenacobius Haran gen. nov., is described to accommodate a clade of species morphologically and phylogenetically distinct from other genera in this tribe. This genus can be diagnosed as follows: protibiae armed with an apical mucro, claws free, eye convexity exceeding the contour of head in dorsal view and forehead with a median furrow. In total, 19 species are recognized in this genus; 14 species are described as new (E. curvisetis Haran gen. et sp. nov.; E. duplicatus Haran gen. et sp. nov.; E. grobbelaarae Haran gen. et sp. nov.; E. hessei Haran gen. et sp. nov.; E. hippopotamorum Haran gen. et sp. nov.; E. kuscheli Haran gen. et sp. nov.; E. mulanjensis Haran gen. et sp. nov.; E. oberprieleri Haran gen. et sp. nov.; E. rectirostris Haran gen. et sp. nov.; E. san Haran gen. et sp. nov.; E. pedi Haran gen. et sp. nov.; E. thoracicus Haran gen. et sp. nov.; E. tsonga Haran gen. et sp. nov. and E. xhosa Haran gen. et sp. nov.), five species of Derelomus Schoenherr (D. atratus Hesse; D. costalis Fåhraeus; D. incognitus Hesse; D. rhodesianus Hesse; D. turneri Marshall) are hereby transferred to Ebenacobius gen. nov. and one species name is placed in synonymy (Derelomus rugosicollis Hesse, 1929 = Derelomus costalis Fåhraeus, 1844 syn. nov.). Members of Ebenacobius gen. nov. seem to develop in inflorescences of dicot plants, with larval stages of at least two species recovered from the flowers of Euclea species (Ebenaceae). A key to the continental African genera of Derelomini and to species of Ebenacobius gen. nov. is provided. Pictures of habitus and terminalia of adults, along with distribution and life history data are also provided for each species.